BE_ZIVILSTRAF ZK 2018 475 vom 10. Januar 2019 - BE Obergericht (2019)
Anfechtung einer Verfügung des kantonalen Handelsregisteramtes, Art. 165 HRegV | Handelsregister/Geschäftsfirmen/kaufmännische Buchführung